The Influence of Headmaster Supervision Role on Teachers’ Competences and Motivation and Its Implication on Teachers’ Performance - Entin Jumantini; Santy Wijaya (Universitas Kuningan, 2020)
Background of the research is begun from the low quality of teachers’ competence andmotivation. This may be the cause of teachers’ performance which is low and lower.Therefore the research is done to find out the influence of headmaster supervision onteachers’ motivation and competences and its implementation on teachers’ performance.The method used in this study was correlation-descriptive design. The population was allEconomy teachers in all state vocational high schools in Kuningan, West java, namely 55teachers from nine state vocational high schools in Kuningan. The instrument wasquestionnaires using Likert scale with five options. The technique used in analyzing thedata was path analysis. All analysis and calculations was done by SPSS Program version20.0.The result of the study were: (1) Headmaster Supervision has a positive influence onTeacher’s Performance with number of coefficient 0,101 (2) Teacher’s Competence hasno significant influence on Teacher’s Performance with number of coefficient 0,360 (3)Teacher’s Motivation has no significant influence on Teacher’s Performance with numberof coefficient 0,157 (4) Headmaster Supervision has a positive influence on Teacher’sCompetence with number of coefficient 0,451, (5) Headmaster Supervision has nosignificant influence on Teacher’s Motivation with number of coefficient 0,220.In short,this study reveals that Headmaster Supervision has an important role in improvingteacher’s competence and give a good impact on teacher’s performance. Therefore, it isrecommended that the headmaster should do some training in supervision to improve thequality of their leadership.Key words: Supervision, Teachers’ Competence, Teachers’ Motivation, Teachers’Performance.